The impact of statins on wound healing: an ally in treating the highly comorbid patient. (1st February 2022) - Abu El Hawa, Areeg A; Klein, Doron; Bekeny, Jenna C; Severin, James H; Zolper, Elizabeth G; Tefera, Eshetu; Evans, Karen K; Fan, Kenneth L; Attinger, Christopher E
Abstract : Objective: To identify the impact that HMG-CoA reductase inhibitors (statins) use has on wound healing outcomes in patients with comorbidities. Method: A retrospective chart review evaluating all new patients presenting to our tertiary wound care centre in 2013 with lower extremity wounds. Patients were divided into two groups depending on whether they took statins or not. Data on wound healing outcomes and wound/patient characteristics were collected. Primary outcomes included healing rate and progression to complete wound healing. Patients were excluded if they had incomplete data or were lost to follow-up before healing status could be confirmed. Results: A total of 194 patients met the inclusion criteria and were allocated to either the statin group (n=89) or to the non-statin group (n=105). Median initial wound size was 0.6cm 3 (Interquartile range (IQR): 0.15–2.4) (p=0.684). In the statin group, 54 (60.6%) patients progressed to complete wound healing compared with 47 (44.7%) in the non-statin group (p=0.027). Median rate of wound healing was 6.7×10 -3 cm 3 /day (IQR: 1.5×10 -3 –2.6×10 -2 ) compared with 3.8×10 - 3cm 3 /day (IQR: 1.7×10 -3 –1.3×10 -2 ) in the non-statin group (p=0.773). Increased age and a higher number of comorbidities were reported in the statin group (p<0.001), respectively). A total of seven patients required amputation: five patients in the statin group and two patients in the non-statin group (p=0.250). Conclusion: This study revealed increased progression to wound healing in patients who were taking statins. The influence of statins on wound healing is promising, but future trials are needed to justify use of this medication class independent of cardiovascular benefit and exclusively for wound healing.